(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
The aim of the study is to understand the heat transfer behavior of low-density nanofibrous layers. Understanding heat transfer through nanofibrous layers embedded with silica aerogel structures will allow us to explore the unique properties of polymer nanofibers for high performance textile applications. It was intended to study the mechanisms of heat transfer through fibrous insulation where the fiber diameter is less than 1 micrometer (0016m). Flexible electrospun PUR and PVDF nanofibrous layers embedded with silica aerogel was produced using electrospinning process. Further, the thermal properties of the electrospun nanofibrous layers embedded with SiO200a0aerogel was analyzed to find their application in enhanced thermal insulation. The thermal properties of the samples were evaluated and statistically analyzed. The microscopic examination confirmed presence of aerogel particles. The results showed enhancement of thermal insulation by increasing the number and the weight per unit area of both nanofibrous layers. The results confirmed that embedding silica aerogel in nanofibrous layers leads increased thermal insulation. From the study, it can be concluded that nanofibrous layers can provide efficient thermal insulation.